Psychoanalytic Knowledge
XII, 253 p.
Keywords: Psychoanalytic Knowledge presents cutting-edge thinking on some fundamental ideas in psychoanalysis by important international scholars in the field of the philosophy of psychoanalysis. It explores the nature of psychoanalytic knowledge in the light of contemporary philosophical views or critiques of a diversity of topics relevant to psychoanalysis: the philosophy of mind; the notion of changing oneself; religion; the notion of interdisciplinary links with psychoanalytic knowledge; post-Freudian psychoanalytic knowledge and challenges to psychoanalytic methodology.